The relationship between fiscal and current account imbalances in OECD economies - Afonso, António (2018)
This study re-examines the nexus between the fiscal balance and the current account balance for 18 OECD countries for the period 1995Q1 to 2018Q1 using panel cointegration, and panel vector autoregressive (VAR) methods. Our results indicate that a strengthening in the fiscal balance by one percentage point of GDP leads to an improvement in the current account balance of about 0.1-0.3 percentage point of GDP. On the other hand, an increase in real government consumption generally leads to a deterioration in the current account balance. The impact of the real effective exchange rate is not statistically significant. The findings also confirm that there is a long-run relationship between the fiscal balance and the current account balance.